Hack proofing Sun Solaris 8 - Miles, Wyman. (Syngress Pub. :, 2001)
The only way to stop a hacker is to think like one! Sun Microsystem's venerable and well-respected operating system Solaris is currently in version 8, and runs on both Intel and Sun Hardware. Solaris is one of the most comprehensive and popular UNIX operating systems available. Hundreds of thousands of business enterprises, both small and large, depend on Sun Solaris to keep their business alive - but have they protected themselves against hackers? Hack Proofing Sun Solaris 8 is the latest addition to the popular Hack Proofing series from Syngress Publishing. Providing hands-on information written by both security professionals and self-proclaimed hackers, this book will give system administrators the edge they need to fortify their Sun Solaris operating system against the never-ending threat of hackers. The fifth title in the popular series that brought us the bestseller Hack Proofing Your Network Teaches strategy and techniques using forensic-based analysis Up to the minute Web-based support with solutions@syngress.com.